Referentiality and the Noun - Anderson, John (HERMES - Journal of Language and Communication in Business, 2011)
This paper argues that nouns and names, as such, do not refer. Apparently-referring nouns and names have been converted lexically to determiners. Thus nouns and names participate in reference by virtue of dependency on a determiner, either in the syntax, as part of a determiner phrase, or lexically, by conversion. Determiners may be partitive (referring to a subset) or non-partitive (generic), and deﬁnite or non-deﬁnite; and various combinations of these subcategories may be expressed either by presence of an independent determiner or by conversion of a noun to a determiner. So, in English, for example, the cows is deﬁnite and partitive; but converted cows may be either non-deﬁnite (partitive or not) or deﬁnite non-partitive (generic). Apparently-referring nouns and names in English are paralleled in some other languages by expressions with a distinct determiner. In French, for instance, conversion is sparing and nouns typically appear with an accompanying determiner: So non-deﬁnite partitive cows corresponds to des vaches in French, and deﬁnite non-partitive cows to (one sense of) les vaches. Greek is intermediate in recourse to conversion. Presence of a determiner and conversion are considered to be alternative strategies (syntactic vs. lexical) for permitting nouns to participate in reference. In the absence of these, nouns are predicative, and languages again vary in how predicativity is expressed – though arguably again involving a determiner. Non-singular predicative nouns are often converted to a non-referential determiner. Singulars may or may not be accompanied by a singular non-referential determiner: compare Greek Ine δikiγoros (‘S/he is lawyer’) with English She is a lawyer.